2018
DOI: 10.1111/jocd.12501
|View full text |Cite
|
Sign up to set email alerts
|

Study of the efficacy of carboxytherapy in alopecia

Abstract: Carboxytherapy seems to be a promising therapeutic option for patchy AA and could be helpful as an adjuvant therapy of AGA but more than 6 sessions are required and adjuvants are recommended for maintenance of the results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 21 publications
3
25
0
1
Order By: Relevance
“…14 Regarding wound healing resulting specifically from chronic venous insufficiency, it is known that the repair process occur slowly, and it is insufficient because the migration of cells is inefficient, which causes the chronicity of this condition as the region cannot be reepithelialised, 15 resulting in dysfunctional tissue in the affected area. 3 The literature on the improvement of this condition does not present concise and recent findings, so we consider the choice of the carboxytherapy in this study because the carbon dioxide used in this process is non-toxic, cost-effective, and safe 16,17 and I II III I II III I II III I II I II III I II III I II III I II respects the principle primum non nocerae (first of all not to prejudice), aiming to stimulate, or at least not inhibit, cell replication. 18 The present study confirmed the decrease of the inflammatory process after treatment with carboxytherapy, which promotes an increase of cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…14 Regarding wound healing resulting specifically from chronic venous insufficiency, it is known that the repair process occur slowly, and it is insufficient because the migration of cells is inefficient, which causes the chronicity of this condition as the region cannot be reepithelialised, 15 resulting in dysfunctional tissue in the affected area. 3 The literature on the improvement of this condition does not present concise and recent findings, so we consider the choice of the carboxytherapy in this study because the carbon dioxide used in this process is non-toxic, cost-effective, and safe 16,17 and I II III I II III I II III I II I II III I II III I II III I II respects the principle primum non nocerae (first of all not to prejudice), aiming to stimulate, or at least not inhibit, cell replication. 18 The present study confirmed the decrease of the inflammatory process after treatment with carboxytherapy, which promotes an increase of cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Doghaim et al, 30 rates. Overall, they found that the mSALT and some dermoscopic parameters improved significantly and quickly, which were persistent, leading to a 100% reduction after the last follow-up session.…”
Section: Alopeciamentioning
confidence: 92%
“…The technique was used by cardiologists in the 1950s to treat patients with peripheral arterial occlusive pathologies. The term “carboxytherapy” was created in 1995 by Luigi Parassoni during the XVI National Meeting of the Italian Society of Aesthetic Medicine 1,2,3…”
Section: Introductionmentioning
confidence: 99%
“…The controlled CO 2 infusion is considered a safe, nonsurgical procedure consisting of applying medicinal carbon dioxide to the skin and adipose tissue 4. Therapeutic indications for CO 2 include vascular, cardiac, metabolic and rheumatic pathologies, cellulitis, chronic wounds, localized adiposities, migraine, stretch marks, wrinkles, unaesthetic scars, and skin laxity 2,5,6,7…”
Section: Introductionmentioning
confidence: 99%